Serum immunoreactive trypsin concentration after a Lundh meal. Its value in the diagnosis of pancreatic disease. Issue 10 (October 1979) - Lake-Bakaar, G; McKavanagh, S; Redshaw, M; Wood, T; Summerfield, J A; Elias, E
Abstract : The changes in serum trypsin concentration have been measured in 47 subjects for up to 2 hours after a Lundh meal. In 18 healthy controls, mean fasting trypsin concentration was 285 +/- 125 ng/ml (mean +/- 2 SD). The maximum increase after the Lundh meal (the trypsin response ratio) was 6.7 +/- 7.5%. Six patients with chronic renal failure had elevated fasting serum trypsin concentrations (range 460-1100 ng/ml) but trypsin response ratios fell within the control range. Of five patients with relapsing pancreatitis, two had raised and three normal or low fasting trypsins. After stimulation two had elevated trypsin response ratios; one of the two had evidence of main duct obstruction. Eleven out of 12 patients with chronic pancreatitis (with or without insufficiency) had low fasting trypsin concentrations (range 0-120 ng/ml) Seven of the 12 also had raised trypsin response ratios. In six patients with cancer of the pancreas, fasting trypsin was low in three, normal in two, and raised in one. Both patients with a normal fasting level had a raised trypsin response ratio. The combination of a single estimation of fasting serum trypsin concentration followed by serial measurements after a Lundh meal provides a useful screening test for chronic pancreatic disease.